2009
DOI: 10.1007/s00726-008-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-ketoglutarate on neutrophil intracellular amino and α-keto acid profiles and ROS production

Abstract: The aim of this study was to determine the effects of alpha-ketoglutarate on neutrophil (PMN), free alpha-keto and amino-acid profiles as well as important reactive oxygen species (ROS) produced [superoxide anion (O(2) (-)), hydrogen peroxide (H(2)O(2))] and released myeloperoxidase (MPO) activity. Exogenous alpha-ketoglutarate significantly increased PMN alpha-ketoglutarate, pyruvate, asparagine, glutamine, asparatate, glutamate, arginine, citrulline, alanine, glycine and serine in a dose as well as duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…AKG may play a similar role in the intestinal immune response. Previous reports have suggested that AKG is an immune enhancer via modulating T cell differentiation and T cell activation [35], managing neutrophil function and generating ROS [5]. AKG activates intestinal innate immunity by improving the expression of α-defensins in the ileum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKG may play a similar role in the intestinal immune response. Previous reports have suggested that AKG is an immune enhancer via modulating T cell differentiation and T cell activation [35], managing neutrophil function and generating ROS [5]. AKG activates intestinal innate immunity by improving the expression of α-defensins in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…It has various physiological functions, including acting as an antioxidant [1, 2] or as an anticancer agent [3, 4] and enhancing host-defense [5]. Recently, AKG has been reported to modulate intestinal energy status, amino acid metabolism, integrity and even immunity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since intracellular pyruvate increases the concentrations of α-ketoglutarate as well as glutamine, glutamate, asparagine, aspartate, alanine, arginine, ornithine, glycine and serine were also significantly elevated in a dose as well as duration of exposure dependent manner. A more precise look at the constitution of PMN amino and α-keto acid changes favour the hypothesis that increases in neutrophil free pyruvate concentrations are mainly followed by pyruvate conversion into important amino and α-keto acid derivatives (Curi et al 1989, 1988; Fuchs et al 1994; Mühling et al 2010, 2007, 2005, 2002). Indeed, our assumption that this metabolisation processes also occurs within PMN cells, may particularly be supported with regard to very similar immunonutritional findings induced by α-ketoglutarate, alanyl-glutamine, ornithine or arginine in other leukocyte cells or even neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…For example α-ketoglutarate, the carbon backbone arising from pyruvate transmission or glutamine oxidation, can immediately be fed into the tricarboxylic acid cycle and through that it is indirectly available to the enzymes of the urea cycle, for example in the form of aspartate via oxaloacetate [1]- [3] [30] [31]. So it is not surprising that α-ketoglutarate, for example incubated in neutrophils is able to increase cellular substrate storages and immune functions [6] [32].…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 99%
“…glucose, alanine, α-ketoglutarate, arginine, ornithine, etc.) or the ability to form energy-rich molecules such as nicotinamide adenine dinucleotide phosphate (NADPH) or guanosine-5'-triphosphate (GTP) from pyruvate-depent pathways, and so on [1]- [6]. Simply one of the most important biochemical processes in which pyruvate is involved, the conversion of pyruvate by the pyruvate dehydrogenase complex (PDH) to form acetyl-CoA, an important link substrate between the metabolic pathways of glycolysis and the citric acid cycle, was, actually and not really surprising to the concerned viewer, also found in neutrophils [7]- [10].…”
Section: Introductionmentioning
confidence: 99%